Insights into mechanisms of UV/ferrate oxidation for degradation of phenolic pollutants: Role of superoxide radicals. (April 2020) - Wu, Shaohua; Liu, Haiyang; Lin, Yan; Yang, Chunping; Lou, Wei; Sun, Jianteng; Du, Cheng; Zhang, Dongmei; Nie, Lijun; Yin, Kai; Zhong, Yuanyuan
Abstract: In this study, the performances and mechanisms of UV/ferrate(VI) oxidation were investigated comprehensively using 2, 4-dichlorophenol (2, 4-DCP) as a probe compound. UV/ferrate(VI) oxidation could efficiently degrade 2, 4-DCP and its oxidation ability outperformed conventional UV-based advanced oxidation processes. Moreover, the degradation process of 2, 4-DCP followed the pseudo-first order kinetics. In the absence of phosphate buffer, the rate constant of 2, 4-DCP degradation increased from 9.4 × 10 −3 to 2.4 × 10 −2 min −1 when pH value was increased from 3.0 to 6.0. However, the degradation was significantly inhibited by phosphate buffer at an identical pH due to the complexation of phosphate with the ferrate(VI) decay products. HCO3 − appreciably accelerated the degradation of 2, 4-DCP, while Cl − showed a negligible effect on the degradation. For the first time, combining with the results of chemical probe method, competitive kinetic experiment, electron spin resonance spectra and radical quenching studies, superoxide radicals were demonstrated as the dominant reactive species responsible for the degradation. On the basis of the intermediates detected by LC-MS/MS analysis, a pathway for 2, 4-DCP degradation was proposed. This study provides a novel approach for contaminant removal using UV/ferrate(VI) oxidation and sheds new insights into the oxidation mechanisms. Graphical abstract: Image 1 Highlights: The oxidation ability of UV/ferrate(VI) was superior to most UV-based AOPs. UV/ferrate(VI) could oxidize 2, 4-dichlorophenol efficiently. Phosphate-buffered system inhibited the efficiency of UV/ferrate(VI) oxidation. Superoxide radicals were main reactive species contributing to the degradation. The generation of superoxide radicals was notably enhanced under UV irradiation.